The Social Movement and Political Exclusion of Fatayat Nahdlatul Ulama as an Islamic Women's Organization in Banten - Yeby Ma’asan Mayrudin; Moh. Rizky Godjali (The Eastasouth Journal of Social Science and Humanities, 2026)
This article aims to discuss issues regarding the activism of the women's organizations of social movement, namely Fatayat NU in handling Covid-19 and describes the manifestations of political exclusion of women-based movements due to patriarchal practices. The research method used a qualitative approach with phenomenological methods. The data collection techniques used were interviews and by document studies. The results from this study show that the activism of the social movement of women's organizations such as Fatayat during the pandemic has an important role to appear deliberately excluded and it is not widely exposed in society. In this study we conducted research limitations, specifically focused on the activism of Fatayat NU's role in handling the impact of Covid-19 and the issue of patriarchy which excluded activism and its movements which were not widely reported by media with limited coverage in the Banten area. In socio-political perspective, this research tries to enrich the knowledge of women's social movement activism in breaking the hegemonic patriarchal culture in society. Also this discourse needs to be carried out massively in order to fight the strength of patriarchy and gender justice.